1961
DOI: 10.1130/0016-7606(1961)72[689:pdobfc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Potassium-Argon Dates of Biotites from Cordilleran Granites

Abstract: Biotites occurring in igneous and metamorphic-metasomatic rocks have been critically studied. The study reveals a marked difference between the chemical composition of biotites from igneous rocks on one hand and those from metamorphic-metasomatic ones on the other. It is concluded that the chemical composition of a biotite reflects the environment of its formation as well as that of the rock containing it. The most frequently occurring ferromagnesian mineral in granites is biotite. As such it is thought that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1962
1962
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…It is conceivable that t z will correlate with the value of 355 M y which Baadsgaard, Folinsbee & Lipson (1961) obtained for the Fitton (Yukon) and Ice Rover (British Columbia) intrusives on the basis of K-Ar dating.…”
Section: Goldfields Region Saskatchewanmentioning
confidence: 89%
“…It is conceivable that t z will correlate with the value of 355 M y which Baadsgaard, Folinsbee & Lipson (1961) obtained for the Fitton (Yukon) and Ice Rover (British Columbia) intrusives on the basis of K-Ar dating.…”
Section: Goldfields Region Saskatchewanmentioning
confidence: 89%
“…These early studies combined with the K-Ar data of Baadsgaard et al (1961) and a Rb-Sr whole-rock isochron (1 15 Ma) for the White Creek batholith (WCB; Fig. 2) obtained by Wanless et al (19686) suggested that most of the plutons in the Purcell Anticlinorium were emplaced in mid-Cretaceous time.…”
Section: Previous Geochronologymentioning
confidence: 95%
“…The Brooks Range Geanticline rose in the late Devonian, accompanied by granitic intrusion (Baadsgaard et al 1961 ;Wanless et al 1966), metamorphism, anddeformation (Norrjs et al 1963). Related clastic sediments with maximum thicknesses reported slightly east of the former Richardson Trough, grade from non-marine to marine and from coarser to finer grained eastward and southeastward from the presumed source in Brooks Range Geanticline (Fig.…”
Section: Late Devonian and Mississippian Deposition And Orogenymentioning
confidence: 97%
“…The K-Ar date needs confirmation, however, because an age of 225 m.y. was obtained from another part of the same granitic body (Baadsgaard et al 1961).…”
Section: Greywackementioning
confidence: 99%